Radicalized - Doctorow, Cory (Tor, 2019)
Told through one of the most on-pulse genre voices of our generation, Radicalized is a timely collection consisting of four SF novellas connected by social, technological, and economic visions of today and what America could be in the near, near future. Unauthorized Bread is a tale of immigration, the toxicity of economic and technological stratification, and the young and downtrodden fighting against all odds to survive and prosper. In Model Minority, a Superman-like figure attempts to rectifiy the corruption of the police forces he long erroneously thought protected the defenseless...only to find his efforts adversely affecting their victims. Radicalized is a story of a darkweb-enforced violent uprising against insurance companies told from the perspective of a man desperate to secure funding for an experimental drug that could cure his wife's terminal cancer. The fourth story, Masque of the Red Death, harkens back to Doctorow's Walkaway, taking on issues of survivalism versus community.